Enhanced elastocaloric effect and mechanical properties of Fe-doped Ni–Mn–Al ferromagnetic shape memory alloys. (September 2019) - Cao, Ting; Xuan, Haicheng; Liu, Shilong; Wang, Libang; Xie, Zhigao; Liang, Xiaohong; Chen, Fenghua; Han, Peide; Wang, Dunhui; Du, Youwei
Abstract: The influence of Fe substitution for Ni on mechanical properties and elastocaloric effect (eCE) in Ni50-x Fex Mn32 Al18 (x = 2, 3 and 4) ferromagnetic shape memory alloys (FSMAs) has been investigated. These alloys undergo a first-order martensitic transformation from B2 (austenite) to L10 (martensite) on the cooling process. As the Fe content increases, the martensitic transformation temperature shifts toward lower temperature region, and the amount of γ phase increases gradually in Ni50-x Fex Mn32 Al18 (x = 2, 3 and 4) alloys. Moreover, the maximum compressive strength (1147 MPa) is obtained in Ni46 Fe4 Mn32 Al18 alloy. The application and removal stress of 300 MPa can produce a large adiabatic temperature change of about 5.1 K and no significant degradation of eCE after 30 stress cycles in Ni46 Fe4 Mn32 Al18 alloy. These results show that Ni50-x Fex Mn32 Al18 alloys would be the promising candidates for new multifunctional materials. Highlights: The effects of alloying with Fe on elastocaloric effect in Ni50-x Fex Mn32 Al18 alloys have been investigated. The amount of γ phase and martensitic transformation temperatures can be turned by controlling the Fe content. The mechanical properties and elastocaloric effect can be effectively enhanced in Ni50-x Fex Mn32 Al18 alloys. A high temperature change of 5 K is obtained at room temperature in Ni46 Fe4 Mn32 Al18 alloy.